The science and theology of Godly love - Lee, Matthew T., 1972-; Yong, Amos; Fauci, Julia; Alexander, Paul (NIU Press, 2012)
Arguing that there are ways to move beyond the limitations of methodological atheism without compromising scientific objectivity, the essays gathered in The Science and Theology of Godly Love explore the potential for collaboration between social science and theology. They do so within the context of the interdisciplinary study of Godly Love, which examines the perceived experience of loving God, being loved by God, and thereby being motivated to engage in selfless service to others. This volume serves as an introduction to and a call for further research in this new field of study, offering ten methodological perspectives on the study of Godly Love written by leading social scientists and theologians. Drawing on the work of Douglas Porpora and others, the contributors contend that agnosticism is the appropriate methodological stance when religious experience is under the microscope. Godly Love does not force a theistic explanation on data, instead these essays show that it sensitizes researchers so that they can take seriously the faith and beliefs of those they study without the assumption that these theologies represent an incontestable truth.